Baseline characteristics, survival and direct costs associated to treatment of gastric cancer patients at the National Oncology Institute of Panama from 2012 to 2015: a hospital-based observational study. Issue 9 (24th September 2017) - Castro, Franz; Shahal, David; Tarajia, Musharaf; Velásquez, Ilais Moreno; Causadias, Maribel Tribaldos; Herrera, Víctor; Gómez, Beatriz; Cukier, Moisés; Motta, Jorge
Abstract : Objectives: Comprehensive epidemiological and economic studies of gastric cancer (GC) in Panama are limited. This study aims to evaluate the association between socioeconomic and clinical variables with survival, describe the survival outcomes according to clinical stage and estimate the direct costs associated to GC care in a Panamanian population with GC. Design and setting: A retrospective observational study was conducted at the leading public institution for cancer treatment in Panama. Participants: Data were obtained from 611 records of patients diagnosed with gastric adenocarcinoma (codes C16.0–C16.9 of the International Classification of Diseases 10th revision), identified between 1 January 2012 and 31 December 2015. Methods: Cox proportional hazards models were used to calculate HRs with 95%  CI to examine associations between the variables and survival. Kaplan-Meier curves were used to assess overall and stage-specific survival. Direct costs (based on 2015 US$) were calculated per patient using standard costs provided by the institution for hospital admission (occupied bed-days), radiotherapy, surgery and chemotherapy, yielding total and overall mean costs (OMC). A comparison of OMC between groups (sex, social security status, clinical stage) was performed applying the bootstrap method with a t-test of unequal variances. Results: An increased risk of dying was observed for patients without social security coverage (HR: 2.02; 95% CI 1.16 to 3.53), overlapping tumours (HR: 1.50; 95% CI 1.02 to 2.22), poorly differentiated tumours (HR: 2.27; 95% CI 1.22 to 4.22) and stage IV disease (HR: 5.54; 95% CI 3.38 to 9.08) (adjusted models). Overall 1-year survival rate was 41%. The estimated OMC of GC care per patient was 4259 US$. No statistically significant differences were found in OMC between groups. Conclusions: Socioeconomic disparities influence GC outcomes and healthcare utilisation. Policies addressing healthcare disparities related to GC are needed, as well as in-depth studies evaluating barriers of access to GC-related services.